2016
DOI: 10.1007/s11664-016-4832-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Shear Strength of Lead-Free Solder Joints with Sn3.0Ag0.5Cu Solder Paste Reinforced with Ceramic Nanoparticles

Abstract: To date, additions of different oxide nanoparticles is one of the most widespread procedures to improve the mechanical properties of metals and metal alloys. This research deals with the effect of minor ceramic nanoparticle additions (SiO 2 , TiO 2 and ZrO 2 ) on the microstructure and mechanical properties of Cu/solder/Cu joints. The reinforced Sn3.0Ag0.5Cu (SAC305) solder alloy with 0.5 wt.% and 1.0 wt.% of ceramic nanoparticles was prepared through mechanically stirring. The microstructure of as-solidified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
7
9
0
Order By: Relevance
“…9), while the calculated average thickness of the entire Cu 6 Sn 5 /Cu 3 Sn layer at the interface was about 3.6 µm ( Table 2). This is in agreement with our recent studies of the Cu 3 Sn/Cu 6 Sn 5 IMCs layer at the interface of SAC305/Cu solder joints [32]. Addition of nanoCo leads to substantial changes in the morphology of the IMC layer at the interface (Fig.…”
Section: Morphology and Growth Of Interfacial Imcs Layer At The Intersupporting
confidence: 93%
“…9), while the calculated average thickness of the entire Cu 6 Sn 5 /Cu 3 Sn layer at the interface was about 3.6 µm ( Table 2). This is in agreement with our recent studies of the Cu 3 Sn/Cu 6 Sn 5 IMCs layer at the interface of SAC305/Cu solder joints [32]. Addition of nanoCo leads to substantial changes in the morphology of the IMC layer at the interface (Fig.…”
Section: Morphology and Growth Of Interfacial Imcs Layer At The Intersupporting
confidence: 93%
“…Similar to our previous studies dealing with nanocomposite SAC solder joints with metal and ceramic nanoadditions, 8,9 a Cu 6 Sn 5 /Cu 3 Sn double layer was observed at the solder/Cu interface. It was found that Ni atoms were incorporated into the Cu 6 Sn 5 crystals, both in the bulk solder and in the interfacial layer, while no regions with either pure Ni or Ni-Sn IMCs could be seen in the joints.…”
Section: Microstructure Analysissupporting
confidence: 88%
“…For instance, a paste and flux mixing method was applied to prepare solders in paste form or as nanocomposite flux-solder mixture, respectively. 7,8,13,14 A conventional planar flow casting 9,15 as well as a roll bonding method 16 have been used to fabricate nanocomposite solder ribbons. The mixing methods are the most popular ones due to the relatively simple experimental procedure; however, during the reflow process the NPs tend to move with the flux, and it is very difficult to estimate the amount of nanoinclusions actually remaining in the solder.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing scientific interest for Sn-based nanocomposite alloys with small additions of various metals, [1][2][3][4] oxides [5][6][7][8] and carbon [9][10][11][12] in nanosized form relates to the possible application of these materials as an alternative to commercial lead-free solders. As pointed out in two literature reviews, [13,14] improved mechanical properties and a reinforced microstructure of solder joints using nanocomposite Sn-Ag-Cu (SAC) alloys compared to those without nanoinclusions, revealed new possibilities for the development of currently used commercial lead-free solders.…”
Section: Introductionmentioning
confidence: 99%